CD7-Positive Diffuse Large B-Cell Lymphoma Presenting as an Intranasal Tumor - Kazuaki Teshima; Masaaki Kume; Yasushi Kawaharada; Takashi Saito; Ko Abe; Sho Ikeda; Hideaki Ohyagi; Megumi Zuguchi; Masashi Zuguchi; Yosuke Kubota; Yoshitaka Enomoto; Masahito Miura; et al. (Case Reports in Hematology)
We report a case of a 74-year-old man with a cluster of differentiation (CD) 7-positive diffuse large B-cell lymphoma (DLBCL) in the right nasal cavity. Flow cytometry analyses showed CD7 and CD20 positivity in tumor cells. The patient received 6 cycles of R-CHOP plus local radiation therapy because positron emission tomography-computed tomography after R-CHOP revealed an intranasal lesion. The patient achieved complete remission (CR) after radiation therapy. The frequency of CD7-positive DLBCL is rare, and only 11 cases with follow-up of clinical course have been reported thus far. CR or partial response was noted in 8 of 11 cases after receiving rituximab combined with chemotherapy. In total, 9 of 12 cases involved the development of extranodal lesions, which occurred as an intranasal tumor in 3 cases. It is important to examine the clinical features by accumulation of further cases.